2011
DOI: 10.15282/ijame.4.2011.7.0037
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Film Condensation of Pure Vapors Flowing Normal to A Horizontal Condenser Tube - Constant Heat Flux at the Tube Wall

Abstract: A mathematical model was developed for the study of external turbulent film condensation of pure vapours flowing downward and normal to the axis of the condenser tube with constant heat flux conditions maintained at the tube wall. The magnitude of interfacial shear was estimated for a given external flow condition of the vapour with the help of Colburn's analogy. The average condensation heat transfer coefficients for different system conditions were evaluated. The present theory was compared with the availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Comprehensive experimental (Zukauskas, 1972), numerical (Jayavel & Tiwari, 2009;Marchi & Hobmeir, 2007;Rahmani, Mirzaee, & Shirvani, 2005;Wang, Penner, & Ormiston, 2000;Wilson & Bassiouny, 2000), and experimental and numerical studies (Matos, Vargas, Laursen, & Bejan, 2004;Sumner, 2010;Rosdzimin, Zuhairi, & Azwadi, 2010) on circular tube banks have been previously conducted. Based on previous studies published in the literature, one can infer from this that the form of a tube and its arrangement has a significant effect on heat transfer (Fowler & Bejan, 1994;Mandhani, Chhabra, & Eswaran, 2002;Vijaya Lakshmi, Subrahmanyam, Dharma Rao, & Sharma, 2011;Suryanarayana, Srinivasa Rao, Reddy Prasad, Sharma, & Sarma,, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Comprehensive experimental (Zukauskas, 1972), numerical (Jayavel & Tiwari, 2009;Marchi & Hobmeir, 2007;Rahmani, Mirzaee, & Shirvani, 2005;Wang, Penner, & Ormiston, 2000;Wilson & Bassiouny, 2000), and experimental and numerical studies (Matos, Vargas, Laursen, & Bejan, 2004;Sumner, 2010;Rosdzimin, Zuhairi, & Azwadi, 2010) on circular tube banks have been previously conducted. Based on previous studies published in the literature, one can infer from this that the form of a tube and its arrangement has a significant effect on heat transfer (Fowler & Bejan, 1994;Mandhani, Chhabra, & Eswaran, 2002;Vijaya Lakshmi, Subrahmanyam, Dharma Rao, & Sharma, 2011;Suryanarayana, Srinivasa Rao, Reddy Prasad, Sharma, & Sarma,, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…However, the thermal conductivity enhancements of Al 2 O 3 and TiO 2 in water are similar, although the heat transfer enhancement of Al 2 O 3 in water is higher than that of TiO 2 in water. However, two groups found that the heat transfer coefficient of nanofluids (Al 2 O 3 and TiO 2 in water and SiC in water) was lower than for pure water for constant average velocity in a turbulent flow (Ferrouillat, 2011;Vijaya Lakshmi, Subrahmanyam, Dharma Rao, & Sharma, 2012). A hybrid nanofluid was used to enhance the heat transfer and pressure drop in a fully developed laminar flow through a uniformly heated circular tube (Suresh, Venkitaraj, Selvakumar, & Chandrasekar, 2012).…”
Section: Heat Transfer Enhancementmentioning
confidence: 99%
“…As reported in the literature, these studies investigate the effects of the different geometries, the change of the dimensions of the bodies and the Reynolds number. In addition to this, the effects of the arrangement types, the number of bodies and the combination of the bodies with different sizes or shapes is also investigated (Akansu, 2004;Ishak, Tahseen, & Rahman, 2013;Satya Narayana, Ramireddy, & Venkataramana, 2011;Tahseen, Ishak, & Rahman, 2012;Vijaya Lakshmi, Subrahmanyam, Dharma Rao, & Sharma, 2011). Bluff body fluid dynamics are widely reported in the literature due to the complexity of the fluid behavior occurring in the back track region of the bodies.…”
Section: Introductionmentioning
confidence: 99%